STRATEGI KEBERHASILAN PPDB DALAM MENARIK MINAT PESERTA DIDIK BARU DI SMA NEGERI 1 SINGKEP - Selamat; Misria Hastuti (TIRAI: Jurnal Program Studi Manajemen Pendidikan Islam, 2025)
This study aims to analyze the success strategies of NewStudent Admissions (PPDB) at SMA Negeri 1 Singkep is attractingprospective students. It employs a qualitative approach with a casestudy method. Data were collected through observation, interviews,and documentation involving the principal, PPDB committee,students, and parents. The findings reveal that the school implementspromotional strategies through social media, printed media, anddirect outreach to junior high schools. The school highlights itsacademic and non-academic programs, extracurricular activities,and improvements in facilities and teaching quality. Factorsinfluencing student interest include the school’s reputation,environmental motivation, strategic location, and affordableeducation costs. The school also provides support such astransportation subsidies and tuition waivers for underprivilegedstudents. The success of these strategies is evidenced by theincreasing number of applicants each year. Despite challenges suchas limited public understanding of online registration systems, theschool addresses them through technical assistance and localservice posts. This research serves as a reference for other schoolsin developing effective, efficient, and inclusive educationalmarketing strategies.